2021
DOI: 10.17576/jsm-2021-5001-12
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Effervescent Tablet-Assisted Dispersive Liquid-Liquid Microextraction with Central Composite Design for Preconcentration of Stimulant Drug

Abstract: The extraction efficiency of stimulant drug, namely caffeine, was investigated using a 23 central composite design. The values of optimum extraction condition were set at 468 μL of 1-dodecanol, 1 piece of effervescent tablet, and 22 °C of extraction temperature. An enrichment factor was calculated as 72 for 80 mL water sample. The run time was conducted in less than 6 min using a non-polar C18 column and an isocratic mobile phase (methanol: water of 40:60 (v/v)) at a controlled flow rate of 1 mL min-1. A good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…A good fitted model should have a minimum R 2 of 80% an R 2 -value that is greater than 0.9 proves a very high degree of correlation [40]. The results of data analysis showed that the R 2 values of the models are 0.96, 0.94, and 0.98 respectively for VMA1, VMA7 and VMAO.…”
Section: Suitability and Adequacy Of Modelsmentioning
confidence: 92%
“…A good fitted model should have a minimum R 2 of 80% an R 2 -value that is greater than 0.9 proves a very high degree of correlation [40]. The results of data analysis showed that the R 2 values of the models are 0.96, 0.94, and 0.98 respectively for VMA1, VMA7 and VMAO.…”
Section: Suitability and Adequacy Of Modelsmentioning
confidence: 92%
“…Tazulazhar et al [65] successfully studies stimulant drugs using CO 2 -effervescent tablet fortified with 1-dodecanol as an extraction solvent. Caffeine was used as a model compound to optimize the extraction process.…”
Section: Application To Determination Of Micropollutants In Environmental Watersmentioning
confidence: 99%